New approach to capture and characterize synaptic proteome - Liu, Xin-An (Proc Natl Acad Sci U S A, 2014)
Little is known regarding the identity of the population of proteins that are transported and localized to synapses. Here we describe a new approach that involves the isolation and systematic proteomic characterization of molecular motor kinesins to identify the populations of proteins transported to synapses. We used this approach to identify and compare proteins transported to synapses by kinesin (Kif) complexes Kif5C and Kif3A in the mouse hippocampus and prefrontal cortex. Approximately 40–50% of the protein cargos identified in our proteomics analysis of kinesin complexes are known synaptic proteins. We also found that the identity of kinesins and where they are expressed determine what proteins they transport. Our results reveal a previously unappreciated role of kinesins in regulating the composition of synaptic proteome.